Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To find the intercepts of the equation [tex]\(2x + 6y = 12\)[/tex], we need to determine the points where the line crosses the x-axis and the y-axis.
1. Finding the x-intercept:
- The x-intercept occurs where the line crosses the x-axis, which means [tex]\(y = 0\)[/tex].
- Substitute [tex]\(y = 0\)[/tex] into the equation [tex]\(2x + 6y = 12\)[/tex].
[tex]\[ 2x + 6(0) = 12 \][/tex]
This simplifies to:
[tex]\[ 2x = 12 \][/tex]
Solving for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{12}{2} = 6 \][/tex]
- Therefore, the x-intercept is [tex]\((6, 0)\)[/tex].
2. Finding the y-intercept:
- The y-intercept occurs where the line crosses the y-axis, which means [tex]\(x = 0\)[/tex].
- Substitute [tex]\(x = 0\)[/tex] into the equation [tex]\(2x + 6y = 12\)[/tex].
[tex]\[ 2(0) + 6y = 12 \][/tex]
This simplifies to:
[tex]\[ 6y = 12 \][/tex]
Solving for [tex]\(y\)[/tex]:
[tex]\[ y = \frac{12}{6} = 2 \][/tex]
- Therefore, the y-intercept is [tex]\((0, 2)\)[/tex].
Given these calculations, the intercepts of the equation [tex]\(2x + 6y = 12\)[/tex] are [tex]\((6, 0)\)[/tex] and [tex]\((0, 2)\)[/tex].
Thus, the correct answer is:
[tex]\[ (6, 0) \text{ and } (0, 2) \][/tex]
1. Finding the x-intercept:
- The x-intercept occurs where the line crosses the x-axis, which means [tex]\(y = 0\)[/tex].
- Substitute [tex]\(y = 0\)[/tex] into the equation [tex]\(2x + 6y = 12\)[/tex].
[tex]\[ 2x + 6(0) = 12 \][/tex]
This simplifies to:
[tex]\[ 2x = 12 \][/tex]
Solving for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{12}{2} = 6 \][/tex]
- Therefore, the x-intercept is [tex]\((6, 0)\)[/tex].
2. Finding the y-intercept:
- The y-intercept occurs where the line crosses the y-axis, which means [tex]\(x = 0\)[/tex].
- Substitute [tex]\(x = 0\)[/tex] into the equation [tex]\(2x + 6y = 12\)[/tex].
[tex]\[ 2(0) + 6y = 12 \][/tex]
This simplifies to:
[tex]\[ 6y = 12 \][/tex]
Solving for [tex]\(y\)[/tex]:
[tex]\[ y = \frac{12}{6} = 2 \][/tex]
- Therefore, the y-intercept is [tex]\((0, 2)\)[/tex].
Given these calculations, the intercepts of the equation [tex]\(2x + 6y = 12\)[/tex] are [tex]\((6, 0)\)[/tex] and [tex]\((0, 2)\)[/tex].
Thus, the correct answer is:
[tex]\[ (6, 0) \text{ and } (0, 2) \][/tex]
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.